Circular economy and paradox theory: A business model perspective. (20th February 2021) - De Angelis, Roberta
Abstract: Business models have become the subject of increasing attention amid management practitioners and researchers since the early nineties and business model innovation has emerged as a distinctive field of academic enquiry. More recently, business model innovation for the circular economy has caught the attention of business leaders and academics alike as the circular economy promises to deliver economic prosperity within ecological limits. Yet research on circular business models is nascent and the business literature gives limited attention to the challenges deriving from circular economy implementation. Using an integrative research approach and particularly, drawing on both paradox theory and circular economy principles and loops, this article provides a preliminary, conceptual systematisation of the typology of organisational tensions in circular economy implementation. It also discusses the relevance of these tensions from a business model perspective. As a result, this article contributes to circular economy research wherein challenges are mostly analysed at the macro level and in the absence of a specific theoretical anchoring. Highlights: Studies of tensions in circular business model implementation are limited. A framework of tensions in circular business model implementation is built. Paradox theory underpins the conceptual framework. Organisational paradoxes are linked to circular economy principles and loops.